2014
DOI: 10.1177/194008291400700307
|View full text |Cite
|
Sign up to set email alerts
|

Ecological Traits of Phyllostomid Bats Associated with Sensitivity to Tropical Forest Fragmentation in Los Chimalapas, Mexico

Abstract: Certain ecological traits of bats may be associated with sensitivity to the fragmentation of their habitat, but the relative importance of this is unclear and has been poorly studied in tropical environments. We evaluated the relationship between six ecological traits of phyllostomid bats (body mass, trophic level, vertical foraging area, natural abundance in continuous forest, wing aspect ratio, and relative wing loading) and three measures of sensitivity to habitat fragmentation (species prevalence, change i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
10
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 66 publications
(211 reference statements)
1
10
0
Order By: Relevance
“…This study corroborates that animalivorous and nectarivorous bats are rarer in disturbed landscapes (see Fenton et al 1992, Wilson et al 1996, Medellín et al 2000, and that these guilds could be good indicators of ecosystem integrity (Rapport 1995). We believe that, together with studies that have been published over the last 20 years (Fenton et al 1992, García-García et al 2014, Farneda et al 2015, we are forming a robust body of evidence about the sensitivity of certain bats to anthropogenic habitat modification in the Neotropics.…”
Section: Relative Contributions Of Different Habitat Types To Abundansupporting
confidence: 82%
See 2 more Smart Citations
“…This study corroborates that animalivorous and nectarivorous bats are rarer in disturbed landscapes (see Fenton et al 1992, Wilson et al 1996, Medellín et al 2000, and that these guilds could be good indicators of ecosystem integrity (Rapport 1995). We believe that, together with studies that have been published over the last 20 years (Fenton et al 1992, García-García et al 2014, Farneda et al 2015, we are forming a robust body of evidence about the sensitivity of certain bats to anthropogenic habitat modification in the Neotropics.…”
Section: Relative Contributions Of Different Habitat Types To Abundansupporting
confidence: 82%
“…, García‐García et al. , Farneda et al. ), we are forming a robust body of evidence about the sensitivity of certain bats to anthropogenic habitat modification in the Neotropics.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Yet, these studies have shown that species richness and abundance differ among strata, and that some species can be classified as either understory or canopy specialists. Canopy foragers appear to be less sensitive to fragmentation than understory species, as they tend to be more mobile due to less evenly distributed resources [29,34,37].Here, we combined extensive ground and canopy mist-netting to explore the effects of forest fragmentation on the vertical stratification of bat assemblages within a landscape-wide fragmentation experiment in the Brazilian Amazon. Specifically, we addressed the following questions:…”
mentioning
confidence: 99%
“…Yet, these studies have shown that species richness and abundance differ among strata, and that some species can be classified as either understory or canopy specialists. Canopy foragers appear to be less sensitive to fragmentation than understory species, as they tend to be more mobile due to less evenly distributed resources [29,34,37].…”
mentioning
confidence: 99%